2021
DOI: 10.12669/pjms.38.1.4465
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of MMP-9 and E-Cadherin in subtypes of Ameloblastoma

Abstract: Background & Objective: Ameloblastomas have been analyzed histologically for diagnostics and its sub-classification; however, the analysis carried out so far does not provide any authentic evidence regarding prognosis of Ameloblastoma. Subject categorization is still a topic of debate. The purpose of this study was to determine the immuno-expression of markers such as MMP-9 and E-Cadherin in different sub-types of ameloblastoma and establish their correlation with histological variants. Methods: Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…However, a variety of cancers, including breast cancer, are associated with the modulation of L-type VGCCs [ 21 ], and the AM stem/progenitor cell marker LGR5 was significantly upregulated in AM, which is similar to the results of a previous study [ 23 ]. The results of immunohistochemical analysis of AM and OKC tissues, including CK10, CK14, E-cadherin, MMP-9, and LGR5, are consistent with those of previous studies [ 23 , 27 , 28 ]. However, we found that CACNA1C was co-expressed with the general progenitor marker CK14 and was negatively correlated with the terminal differentiation marker CK10 in AM.…”
Section: Discussionsupporting
confidence: 92%
“…However, a variety of cancers, including breast cancer, are associated with the modulation of L-type VGCCs [ 21 ], and the AM stem/progenitor cell marker LGR5 was significantly upregulated in AM, which is similar to the results of a previous study [ 23 ]. The results of immunohistochemical analysis of AM and OKC tissues, including CK10, CK14, E-cadherin, MMP-9, and LGR5, are consistent with those of previous studies [ 23 , 27 , 28 ]. However, we found that CACNA1C was co-expressed with the general progenitor marker CK14 and was negatively correlated with the terminal differentiation marker CK10 in AM.…”
Section: Discussionsupporting
confidence: 92%